Supplement to Natural Resources of India and Organisation for their Coordinated Survey, Assessment and Studies - Planning Commission (Planning Commission)
Adequate and continuing inventories of the renewable natural resources of the nation are needed to determine their condition, productivity, and potential use in relation to human needs and should be supported as a guide to the proper utilization and treatment of these resources.
Planning Commission